MICROSTRUCTURAL CHARACTERIZATION OF CP STEEL USED IN AUTOMOTIVE INDUSTRY - Dias, Erica [UNESP]; Horimoto, Lais; Pereira, Marcelo; Hotza, D. (Trans Tech Publications Ltd, 2014)
This study aims to characterize the microstructure of the complex phase steel (CP). Using the conventional and colored metallographic analysis with 3% Nital etchant, sodium metabisulfite 10% and LePera. Techniques were applied in this work of optical microscopy, using, besides the lighting in bright field, dark field illumination of the reverse contrast in bright field illumination, the method of polarized light, which generates colorful contrast, providing a complementary identification phases present in the microstructure, and the system by differential interference contrast (DIC). The results obtained by metallography CP indicates that the steel has a microstructure composed of ferrite, retained austenite, bainite and martensite and precipitates arranged in a refined and complex morphology. Besides bright field illumination others' optical microscopy's techniques such as dark field illumination were applied.
Keywords: CP Steel; Metallography; Microstructural characterization